2015
DOI: 10.1016/j.jff.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of anthocyanin-rich Queen Garnet plum juice reduces platelet activation related thrombogenesis in healthy volunteers

Abstract: Available online A B S T R A C TThe anti-thrombotic properties of an anthocyanin-rich Queen Garnet plum juice (QGPJ) and anthocyanin-free prune juice (PJ) were studied in this randomised, double-blind, crossover trial. Twenty-one healthy subjects (M = 10, F = 11) consumed QGPJ, PJ or placebo, 200 mL/ day for 28-days followed by a 2-week wash-out period. Only QGPJ supplementation inhibited platelet aggregation induced by ADP (<5%, P = 0.02), collagen (<2.7%, P < 0.001) and arachidonic acid (<4%, P < 0.001); red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 50 publications
1
44
1
1
Order By: Relevance
“…The beneficial health effects of these levels of anthocyanin found in the Queen Garnet plum are currently being researched. Preliminary studies using this variant of plum have demonstrated antithrombotic activity in humans (Santhakumar et al, 2015a) and a beneficial effect on metabolic syndrome in rat models, in vivo and in vitro bioactivity (Bhaswant et al, 2015). It is important that similar studies be performed with different hybrids of plum to confirm their beneficial health effects in the fight against chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial health effects of these levels of anthocyanin found in the Queen Garnet plum are currently being researched. Preliminary studies using this variant of plum have demonstrated antithrombotic activity in humans (Santhakumar et al, 2015a) and a beneficial effect on metabolic syndrome in rat models, in vivo and in vitro bioactivity (Bhaswant et al, 2015). It is important that similar studies be performed with different hybrids of plum to confirm their beneficial health effects in the fight against chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who received either the single dose or a glass of water on empty stomach in the morning showed significant reduction in both systolic and diastolic blood pressure, while the double dose was associated with only a reduction in systolic blood pressure. The control (water) group also had significant increase in serum high-density lipoprotein that was not seen by prune-treated groups Plum juice supplementation with the novel-bred Queen Garnet plum that has higher anthocyanin concentrations than the usual variant (Santhakumar et al, 2015a) observed an inhibition of platelet aggregation induced by adenosine diphosphate, collagen and arachidonic acid.…”
Section: Cardiovascular Disease Risk Factorsmentioning
confidence: 97%
“…[45]. For the anthocyanin, cyanidin-3-glucoside, which is the main anthocyanin in QGP juice [36,46], the half-life has been shown to range between 12 and 51h [47].…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…However direct antioxidant benefits of flavonoids, at physiological concentration in vivo have not been completely determined [13]. Short term intervention studies examining the effects of individual flavonoids or flavonoid-rich foods on circulating oxidative stress biomarkers in vivo have been inconsistent, with some showing no effect [14][15][16], and others some benefits [17][18][19][20]. Evidence published linking dietary flavonoid intake to antioxidant status is limited and to date, few observational studies have address this effect.…”
Section: Introductionmentioning
confidence: 99%